Silver Antibacterial Synergism Activities with Eight Other Metal(loid)-Based Antimicrobials against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus - Ali Pormohammad; Raymond J. Turner (MDPI AG, 2020)
The present study surveys potential antibacterial synergism effects of silver nitrate with eight other metal or metalloid-based antimicrobials (MBAs), including silver nitrate, copper (II) sulfate, gallium (III) nitrate, nickel sulfate, hydrogen tetrachloroaurate (III) trihydrate (gold), aluminum sulfate, sodium selenite, potassium tellurite, and zinc sulfate. Bacteriostatic and bactericidal susceptibility testing explored antibacterial synergism potency of 5760 combinations of MBAs against three bacteria (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus) in three different media. Silver nitrate in combination with potassium tellurite, zinc sulfate, and tetrachloroaurate trihydrate had remarkable bactericidal and bacteriostatic synergism effects. Synergism properties of MBAs decreased effective antibacterial concentrations remarkably and bacterial cell count decreased by 8.72 log10 colony-forming units (CFU)/mL in E. coli, 9.8 log10 CFU/mL in S. aureus, and 12.3 log10 CFU/mL in P. aeruginosa, compared to each MBA alone. Furthermore, most of the MBA combinations inhibited the recovery of bacteria; for instance, the combination of silver nitrate-tetrachloroaurate against P. aeruginosa inhibited the recovery of bacteria, while three-fold higher concentration of silver nitrate and two-fold higher concentration of tetrachloroaurate were required for inhibition of recovery when used individually. Overall, higher synergism was typically obtained in simulated wound fluid (SWF) rather than laboratory media. Unexpectedly, the combination of A silver nitrate-potassium tellurite had antagonistic bacteriostatic effects in Luria broth (LB) media for all three strains, while the combination of silver nitrate-potassium tellurite had the highest bacteriostatic and bactericidal synergism in SWF. Here, we identify the most effective antibacterial MBAs formulated against each of the Gram-positive and Gram-negative pathogen indicator strains.